Reducing the Vulnerability of Azerbaijan?s Agricultural Systems to Climate Change: Impact Assessment and Adaptation Options - Ahouissoussi, Nicolas (World Bank, 2015)
Agriculture is one of the most climate-sensitive of all economic sectors. Azerbaijan is one of the many countries where the majority of the rural population depends on agriculture?directly or indirectly?for their livelihood. Further, changes in climate and their impacts on agricultural systems and rural economies are already evident throughout Europe and Central Asia. The risks associated with climate change therefore pose an immediate and fundamental problem in the country.